PENDIDIKAN KESEHATAN TENTANG PEMANFAATAN SOSIAL MEDIA YANG BAIK PADA REMAJA - Inge Anggi Anggarini (Khidmah, 2021)
The very rapid development of social media lately can be a hot topic to discuss because many people use social media but they do not understand social media itself. Unfortunately, most internet users do not understand the legal implications of using social media as a forum to write things that harm others, such as slandering, distorting facts and spreading false news. The community service activities that will be carried out are entitled health education about the good use of social media in adolescents. The purpose of this activity is to increase teenagers' understanding of how to use social media properly so that teenagers can have positive interactions on social media and can pay attention to ethics in interacting. This is very important so that all adolescent activities on social media do not have a negative impact on life, either directly or indirectly. This activity was carried out in September-October 2021 at IKest Muhammadiyah Palembang with a total of 57 respondents. During this 2-month period, several stages of preparation and coordination with related parties will be carried out and conduct health education for students of IKesT Muhammadiyah Palembang